Double labelling immunohistochemistry on the sympathetic trunk ganglia neurons projecting to the extrinsic penile smooth musculature of the pig: an experimental study on the retractor penis muscle - Botti, Maddalena; Gazza, Ferdinando; Ragionieri, Luisa; Bo Minelli, Luisa; Panu, Rino (Italian Journal of Anatomy and Embryology, 2013)
Retrograde neuronal tracing and double labelling immunofluorescence methods were used to define the neurochemical content of sympathetic trunk ganglia neurons projecting to the pig retractor penis muscle, which was taken as an experimental model of the male genital smooth musculature. After the injection of Fast Blue into the bulbo-penile portion of the retractor penis muscle, the eventual co-existence of the catecholaminergic marker tyrosine hydroxylase with calcitonine gene related peptide, leu-enkephalin, neuropeptide Y, neuronal nitric oxide synthase, substance P, vasoactive intestinal polypeptide or vesicular acetylcholine transporter was studied in the ipsilateral S1 sympathetic trunk ganglia, which resulted to contain the greatest number of autonomic retractor penis muscle projecting cells. The observation of Fast Blue positive neurons under the fluorescent microscope allowed the identification of different subpopulations of catecholaminergic and non-catecholaminergic retractor penis muscle-projecting neurons. The majority of catecholaminergic cells contained tyrosine hydroxylase alone, while the remaining part showed co-localization of tyrosine hydroxylase with all the other tested markers. These last neurons were immunoreactive, in decreasing percentages, for neuropeptide Y, leu-enkephalin, neuronal nitric oxide synthase, substance P, calcitonine gene related peptide, vasoactive intestinal polypeptide and vesicular acetylcholine transporter. The majority of non-catecholaminergic neurons were immunonegative for all the tested markers. The remaining non-catecholaminergic cells contained, in decreasing percentages, neuropeptide Y, neuronal nitric oxide synthase, leu-enkephalin, vasoactive intestinal polypeptide, vesicular acetylcholine transporter, substance P and calcitonine gene related peptide. Our findings documented the complexity of the neurochemical interactions that regulate both the motor functions of RPM and the blood flow through the muscle.